Nonlinear systems stability analysis : Lyapunov-based approach - Nikravesh, Seyed Kamaleddin Yadavar (Boca Raton : CRC Press, 2013)
"The dynamic properties of a physical system can be described in terms of ordinary differential, partial differential, difference equations or any combinations of these subjects. In addition, the systems could be time varying, time invariant and/or time delayed, continues or discrete systems. These equations are often nonlinear in one way or the other, and it is rarely possible to find their solutions. Numerical solutions for such nonlinear dynamic systems with the analog or digital computer are impractical. This is due to the fact that a complete solution must be carried out for every possible initial condition in the solution space. Graphical techniques which can be employed for finding the solutions of the special cases of first and second order ordinary systems, are not useful tools for other type of systems as well as higher order ordinary systems"--
Basic Concepts. Stability Analysis of Autonomous Systems. Stability Analysis of Nonautonomous Systems. Stability Analysis of Time-Delayed Systems. An Introduction to Stability Analysis of Linguistic Fuzzy Dynamic Systems. References. Appendices. Index.
Includes bibliographical references and index.
Keywords: Nonlinear control theory; Lyapunov stability; SCIENCE / Chemistry / Industrial & Technical; TECHNOLOGY & ENGINEERING / Electrical; TECHNOLOGY & ENGINEERING / Quality Control